Evaluation of a novel database for quality assurance at a head and neck service in New Zealand: an audit of free flap head and neck reconstruction. Issue 7 (21st May 2020) - Marinone Lares, Silvia G.; Clark, Sita; Mathy, Jon A.; Chaplin, John; McIvor, Nick
Abstract: Background: Clinical audit is a critical quality improvement exercise, yet efficient audit tools are lacking. The main objective of this study was to evaluate a recently deployed database in facilitating the process of clinical audit, and the secondary objective was to evaluate the outcomes of free flap reconstruction of the head and neck at our centre. Methods: A head and neck cancer‐specific database was customized to suit the needs of our head and neck multidisciplinary team. Data has been entered prospectively into this database since March of 2018. An audit of free flap reconstruction of the head and neck over a 12‐month period was performed using the database and analysed as a case study to examine its efficacy as a clinical audit tool. Additionally, the outcomes of free flap reconstruction at our centre were compared to those reported in the international literature. Results: The database allows flexible and specific queries, analysis and export of data, and can provide immediate results. However, issues with data quality and completeness were identified. In this audit, the overall 30‐day complication rate and 30‐day mortality in patients undergoing free flap reconstruction of the head and neck were 58% and 3%, respectively. Conclusion: The database is fit for its intended purpose as an audit tool. Outcomes of free flap reconstruction of the head and neck at our centre are comparable to those of institutions overseas.